1970
DOI: 10.2135/cropsci1970.0011183x001000060003x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stresses Which May Limit Soybean Yields1

Abstract: Hydroponically grown ‘Dare’ soybeans (Glycine max L.) were exposed to a number of discrete stresses at the time of flowering. Effects on initial pod set, subsequent pod abscission, and ovule growth were assessed. Lodging, when not associated with shading, did not lower pod set. Severe short‐term deficiency of calcium and nitrogen decreased pod set by one‐third. Temperatures above 40C caused severe pod abscission. Shading (63% of ambient) also caused abscission of half the pods. If plants were returned to short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
5

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 0 publications
2
47
0
5
Order By: Relevance
“…During this period, the mean (28.4ºC), daily maximum (33.3ºC) and daily minimum temperatures (24.9ºC) were about 2ºC higher in 2010 than in 2008, and this period corresponded to R1 to R3 of both cultivars. During flowering and pod set, temperatures as high as 30/20ºC (day/night) were favorable for pod set, but temperatures above 40ºC severely decreased pod formation (Mann and Jaworski, 1970). Seed formation was decreased as the day temperature increased from 30ºC to 35ºC (Gibson and Mullen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…During this period, the mean (28.4ºC), daily maximum (33.3ºC) and daily minimum temperatures (24.9ºC) were about 2ºC higher in 2010 than in 2008, and this period corresponded to R1 to R3 of both cultivars. During flowering and pod set, temperatures as high as 30/20ºC (day/night) were favorable for pod set, but temperatures above 40ºC severely decreased pod formation (Mann and Jaworski, 1970). Seed formation was decreased as the day temperature increased from 30ºC to 35ºC (Gibson and Mullen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on pod setting as influenced by low temperature in the flowering stage (Saito et aI, 1970; Duke et aI, 1979;Hume and Jackson, 1981; Hayashi et aI, 1998). Exposing soybeans to a low temperature affects a wide range of physiological processes, including photosynthesis (Duke et aI, 1979; Marowitch, et a11986; Purcell et aI, 1987; Wang et aI, 1997), carbohydrate metabolism (Thomas et al, 1981; Marowitch et aI, 1986; Purcell et aI, 1987), nitrogen fixation (Duke et aI, 1979;Takahashi and Asanuma, 1996), and pollination (Goto and Yamamoto, 1972).Shading reduces the number of pods (Mann and Jaworski, 1970; Tanaka et aI, 1980; Ishikawa et aI, 1984;Jiang and Egli, 1993) and the amount of nitrogen accumulation because of a reduction in nodule and root growth in the soybean plant (Tanaka et aI, 1980). …”
mentioning
confidence: 99%
“…Shading reduces the number of pods (Mann and Jaworski, 1970;Tanaka et aI, 1980;Ishikawa et aI, 1984;Jiang and Egli, 1993) and the amount of nitrogen accumulation because of a reduction in nodule and root growth in the soybean plant (Tanaka et aI, 1980). Plalll Prod uction Science Vol.…”
mentioning
confidence: 99%
“…Plant response to high temperature was most severe during the periods of rapid growth and development. Mann and Jaworski (1970) reported that flowers abscission of soybean cultivars in the polythene house was reduced due to higher temperature where air temperature above 40 o C caused severe pod abscission. …”
Section: Weight Of 100 Seedmentioning
confidence: 99%
“…Soybean seed yield increased as the day/night temperature increased between 18/12°C and 26/20°C, but yield decreased when plants were grown at temperature greater than 26/20°C (Huxley et al, 1976). Raising temperature from 29°C to 34°C during seed fill decreased soybean seed yield (Dornobos and Mullen, 1991).Temperature above 40°C causes severe pod abortion in soybean (Mann and Jaworski, 1970). High temperature accelerate the abscission process of developing the reproductive organs and affect in pod set and yield in soybean (Saito et al, 1970;Ashley and Ethridge, 1978;Korte et al, 1983).…”
Section: Introductionmentioning
confidence: 99%